Evaluation of cytotoxic activity of marine fungi isolated from sponges in Nha Trang bay - Phan Thi, Hoai Trinh; Yurchenko, Ekaterina A.; Yurchenko, Anton N.; Ngo Thi, Duy Ngoc; Vo Thi, Dieu Trang; Cao Thi, Thuy Hang; Tran Thi, Thanh Van; Pham Duc, Thinh; Huynh Hoang, Nhu Khanh; Le Dinh, Hung; et al. (Vietnam Journal of Marine Science and Technology, 2022)
Marine fungi are evaluated as a potential source for new natural compounds with bioactivities of pharmaceutical values. In this study, 66 fungal strains, isolated from 37 sponge samples in Nha Trang bay, were determined for cytotoxic activity against two human cancer cell lines, including cervical cancer (Hela) and breast cancer (MCF-7) cells using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. The results showed that 46.9% (31/66) strains exhibited cytotoxic activity against both test cancer cell lines. Based on the internal transcribed spacer (ITS) gene sequences analysis, five isolates with significant anticancer activity were identified as Aspergillus sp. 1901NT-1.2.2, Talaromyces sp. 1901NT-1.39.3, Aspergillus subramanianii 1901NT-1.40.2, Phoma sp. 1901NT-1.45.1, and Penicillium sp. 1901NT-2.53.1. Our finding indicated that the sponge-derived fungi in Nha Trang bay might be a potential source for anticancer compounds and need further study to discover new anticancer drugs.